Evaluation of Crisis Handling of Carasun Cosmetic Company - Reksananda Shindy Priskila; Dwi Prasetyo (LPPM Stikosa-AWS, 2023)
Threats to a company's existence can arise from a reputation crisis induced by various factors. If not handled carefully, such a reputation crisis can lead to a loss of trust from customers, investors, and employees, which, in turn, can have a detrimental impact on the overall company's performance. For example, Carasun, a cosmetics company, faced a reputation crisis due to allegations of using